Impact of marketing communication mix towards image, brand awareness, and costumers decision to choose Islamic insurance - Fajar, Ade; Sobari, Nurdin; Usman, Hardius (Journal of Islamic Economics Lariba, 2018)
This study aims to determine the effect of marketing communication mix on brand image and brand awareness and its implication on the consumer decision to choose sharia insurance. This research is descriptive by using quantitative approach method and also supported by qualitative data. Data analysis method used in this research is SEM (Structural Equation Modeling). Respondents in this study are sharia life insurance customer in Jakarta, Bogor, Depok, Tanggerang, and Bekasi with a sample of 160 people. The result of the research shows that marketing communication mixes influence to brand image, marketing communication mix influence to brand awareness, marketing communication mix does not affect consumer decision to choose sharia insurance, brand image influence to consumer decision to accept sharia insurance, and brand awareness influence to consumer decision sharia insurance.